2004
DOI: 10.1211/0022357022511
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the precipitation of poorly soluble weak bases upon entry in the small intestine

Abstract: Solubility and dissolution relationships in the gastrointestinal tract can be critical for the oral bioavailability of poorly soluble drugs. In the case of poorly soluble weak bases, the possibility of drug precipitation upon entry into the small intestine may also affect the amount of drug available for uptake through the intestinal mucosa. To simulate the transfer out of the stomach into the intestine, a transfer model was devised, in which a solution of the drug in simulated gastric fluid is continuously pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
212
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(223 citation statements)
references
References 16 publications
6
212
1
4
Order By: Relevance
“…For the specific case of poorly soluble weak bases like MC, one must not only consider solubility and dissolution but also the possibility of precipitation as the drug moves from the favorable pH conditions in the stomach to a less favorable pH environment in the small intestine. As the pH approaches or even exceeds the pKa of the basic drug, its solubility undergoes a sharp decrease and the concentration of the drug may in fact exceed the solubility (Kostewicz et al, 2004). The question is does the drug stay in supersaturated solution till complete absorption occurs or does it precipitate and become no longer available for absorption.…”
Section: Transfer Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For the specific case of poorly soluble weak bases like MC, one must not only consider solubility and dissolution but also the possibility of precipitation as the drug moves from the favorable pH conditions in the stomach to a less favorable pH environment in the small intestine. As the pH approaches or even exceeds the pKa of the basic drug, its solubility undergoes a sharp decrease and the concentration of the drug may in fact exceed the solubility (Kostewicz et al, 2004). The question is does the drug stay in supersaturated solution till complete absorption occurs or does it precipitate and become no longer available for absorption.…”
Section: Transfer Modelmentioning
confidence: 99%
“…In this model, a solution of the drug dissolved in the simulated gastric fluid is allowed to transfer into simulated intestinal fluid at a suitable rate of (0.5-9 ml/min) under paddle rotation. Drug precipitation in the acceptor medium is examined via concentration time measurements (Kostewicz et al, 2004). This is performed under both fasting and fed conditions.…”
Section: Transfer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Garbacz et al have also showed diclofenac and nifedipine drug dissolution profiles to be predicted using a dissolution apparatus that mimics in vivo physical stresses [146,147]. Kostewicz et al [148] also developed a two-compartmental apparatus using a peristaltic pump using fasted and fed state-simulated media. Their sampling was performed manually with a syringe filtration step and a high-performance liquid chromatography analysis.…”
Section: Dissolution Apparatusesmentioning
confidence: 99%
“…Also, pH was also not raised back to the original value as it was maintained only by the action of the contained buffer. In the second apparatus, however, pH, volume and the composition of the duodenal fluid were all left without intervention [65,148]. Psachoulias et al [149] presented an improved method, where although a gastric and a duodenal compartment were used, the dilution of the duodenal fluid which was the FaSSIF V2 plus was compensated by an inflow of a concentrated medium from a third vessel.…”
Section: Dissolution Apparatusesmentioning
confidence: 99%